Integrative Therapies for Magnesium and Calcium Deficiency in a Food Insecure, Autism Subject: A Case Report. - Hollywood, Jasmine B. (Integrative Medicine: A Clinician's Journal)
Introduction: Individuals facing homelessness with autism spectrum disorder (ASD) are at increased risk for food insecurity. Financial difficulties increase the demand to donate blood plasma to support hardship. Excessive blood plasma donations may lead to micronutrient deficiencies exacerbating deficits derived from poor food habits. Therapies that may support these populations in securing foods and improving lifestyle habits may be diet, supplements, nutrition education, and holistic lifestyle recovery support group. Case Description: A homeless, 31-yr-old Caucasian female with ASD presenting with magnesium and calcium deficiencies, and ten year history of blood plasma donations sought medical nutrition therapy. Over 6 months and in conjunction with physician prescriptions, interventions were augmented with magnesium and calcium supporting vegetables; reduction of dairy, fast foods, and ultra-processed foods; nutrition education and holistic lifestyle recovery support group. Upon final visit, the patient had remarkable improvement of nutrition knowledge and food budgeting, in-kitchen housing stability, food access, and stress reduction. Conclusion: Nutrition education improves nutrition knowledge and food budgeting facilitating food access, while holistic lifestyle recovery support groups can influence healthier living and stress reduction in homeless patients with ASD. Population-based clinical studies should be done to understand the role of these conjunctive therapies to support nutrition practice.